This is Interesting! High-Performance Work Systems, Empowering Leadership and Burnout for Employee Job Satisfaction - Sofyan, Joel Faruk; Aulia, Shifa; Fajarwati, Diana (Jurnal Ilmiah Sumber Daya Manusia, 2024)
Currently, industrial competition has found many problems that cause business failure. This business failure can be overcome by preparing superior and good employees or human resources. Lack of job satisfaction certainly has a big impact on the development of the company. This study examines the influence of HPWS, Burnout and Empowering Leadership on Job satisfaction in automotive companies in Indonesia. This research is quantitative research. Data collection was conducted online starting in 2023, using google form which resulted in 295 selected respondents. The survey data were then analysed using the Partial Least Square - Structural Equation Model (PLS-SEM) method. The findings of this study indicate that, HPWS has a positive effect on Burnout, HPWS has a positive effect on Job satisfaction, Empowering leadership has no significant effect on Burnout, Empowering leadership has a positive effect on Job satisfaction, Burnout has no significant effect on Job satisfaction and Burnout does not significantly moderate the relationship of HPWS on Job satisfaction.  This study provides managerial implications for moving companies, to be able to increase motivation and direction so that employees feel they belong to the company and generate personal commitment to achieving goals with management. A comfortable work environment will also make employees feel comfortable at work and can continue to improve employee performance in the company.